Acute Oral Toxicity, Antioxidant Activity and Molecular Docking Study of 2-(4-Bromo-phenoxy)-N-[6-chloro-4-(4-chlorophenyl)-3-cyano-4H-chromen- 2-yl]-acetamide - Chauhan, Divya; Agrawal, Anurag; Sahu, Jagdish K.; Kumar, Sushil (Current Drug Discovery Technologies, 2024)
Background: Several studies have been conducted on 4-H chromene compounds because of their intriguing pharmacological and biological properties. Various new natural compounds having a chromene foundation have been reported over the past 20 years. Objective: In the present study, we reported the acute oral toxicity, antioxidant activity, and molecular docking study of the most active 4H-chromene derivative2-(4-Bromo-phenoxy)-N-[6-chloro-4-(4- chlorophenyl)-3-cyano-4H-chromen-2-yl]-acetamide (A9). Method: The acute oral toxicity was carried out as per OECD 423 guidelines. For investigating the antioxidant activity, various biochemical parameters in colon tissue like SOD, CAT, MDA, PC and GSH and also enzyme levels, such as ALT, AST, ALP, and LDH, were measured in this experiment. Results: Acute oral toxicity study indicated that the A9 ligand was found to be safer in animals. Additionally, the A9 ligand had significant antioxidant properties at various doses and was not found to be harmful to the liver. Due to its stronger binding energy and the appropriate interactions that induce inhibition, the A9 ligand's antioxidant function was also validated by additional molecular docking research. Conclusion: This compound can be exploited as a lead molecule in further research.
Keywords: antioxidant activity